Bile acid absorption kinetics in Crohn's disease on elemental diet after oral administration of a stable-isotope tracer with chenodeoxycholic-11, 12-d2 acid. Issue 9 (September 1982) - Nishida, T; Miwa, H; Yamamoto, M; Koga, T; Yao, T
Abstract : A non-radioactive tracer, deuterium, incorporated in chenodeoxycholic acid, was used to study bile acid absorption kinetics employing gas chromatography-mass fragmentography for its analysis. Eight patients with Crohn's disease and four control volunteers were administered chenodeoxycholic-11, 12-d2 acid. In order to obtain constant dietary conditions, they were fed by an elemental diet during the study. There were significant reductions of the biological half-life of chenodeoxycholic-11, 12-d2 acid, the pool size of chenodeoxycholic acid, and the total bile acid pool size in patients with Crohn's disease as compared with those in normal subjects. There was a marked increase in the relative concentration of ursodeoxycholic acid with a concomitant decrease of deoxycholic acid in patients with Crohn's disease, although such differences did not reach statistical significance. The present study confirms that there are some impairments of enterohepatic circulation of bile acids in patients with Crohn's disease.